Successful Pregnancy in a Patient with Ebstein’s Anomaly: A Rare Case Report - Sharmin, Most Arifa; Begum, Firoza (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Ebstein’s anomaly, a rare congenital heart disease, occurring in 1 in 20,000 live births. The leaflets are placed deeper into the right ventricle instead of the normal position. Pregnancy however is well tolerated and the maternal risks of pregnancy co-relates well with the degree of tricuspid regurgitation, right ventricular function and presence of cyanosis. Aim is to emphasize the meticulous follow-up with fetal & maternal medicine specialist with multidisciplinary approach can give a successful outcome. Proper diagnosis and meticulous follow-up with good ANC have made this case, pregnancy with Ebstein’s anomaly successful. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 68-70